Rhodium‐Catalyzed Alkene Hydrosilylation via a Hydride Shuttle Process by Diene Ligands: Dramatic Enhancement of Regio‐ and Diastereoselectivity1. Issue 27 (21st August 2014) - Hua, Yuanda; Nguyen, Hiep H.; Trog, Gabriela; Berlin, Adam S.; Jeon, Junha
Abstract: A cooperative ligand‐assisted, Rh‐catalyzed intramolecular alkene hydrosilylation of homoallylic silyl ethers (1 ) was developed to provide 1, 3‐ trans ‐oxasilacyclopentanes ( trans ‐2 ) in a highly regio‐ and diastereoselective manner. The modification of metal‐ligand architecture employing an inner‐sphere functional diene ligand (1, 3‐cyclohexadiene) and a supporting phosphine ligand (BINAP) was identified as responsible for dramatic enhancement of selectivities. Mechanistic details of a diene ligand‐mediated hydride shuttle process are presented as the potential mechanistic driving force behind the high level of the selectivities. Abstract : A cooperative functional diene ligand and a supporting phosphine ligand mediated, Rh‐catalyzed intramolecular alkene hydrosilylation of homoallylic silyl ethers was developed to provide 1, 3‐ trans ‐oxasilacyclopentanes in a highly regio‐ and diastereoselective manner. A diene ligand mediated hydride shuttle process is proposed as the mechanistic driving force behind the high level of selectivities.